Thirty‐day mortality with andexanet alfa compared with prothrombin complex concentrate therapy for life‐threatening direct oral anticoagulant‐related bleeding. Issue 2 (5th March 2022) - Cohen, Alexander T.; Lewis, Megan; Connor, Augusta; Connolly, Stuart J.; Yue, Patrick; Curnutte, John; Alikhan, Raza; MacCallum, Peter; Tan, Joachim; Green, Laura
Abstract: Objective: Compare 30‐day mortality among patients receiving the specific reversal agent andexanet alfa versus replacement prothrombin complex concentrate (PCC) in the management of direct‐acting oral anticoagulant (DOAC)–related bleeds. Methods: Two patient‐level datasets were used: ANNEXA‐4, a prospective, single‐arm trial of patients taking apixaban or rivaroxaban who received andexanet alfa and ORANGE, a prospective, observational study of anticoagulated patients in UK hospitals, some of whom received PCC. Patients were propensity score matched based on demographic and clinical characteristics. Subgroup analyses were performed by bleed type (intracranial hemorrhage [ICH], gastrointestinal [GI], other). Relative risk (RR) of all‐cause 30‐day mortality was calculated. Results: 322 ANNEXA‐4 patients treated with andexanet alfa (mean age = 77.7 years; 64.9% ICH) were matched with 88 ORANGE patients treated with PCC (mean age = 74.9 years, 67.1% ICH). Adjusted 30‐day mortality for patients treated with andexanet alfa (14.6%) was lower than patients treated with PCC (34.1%; RR, 0.43; 95% CI, 0.29–0.63). In the ICH subgroup, patients treated with andexanet alfa had lower mortality (15.3%) than patients treated with PCC (48.9%; RR, 0.31; 95% CI, 0.20–0.48). Mortality risk was lowest for patients in the GI subgroup but did not differ significantly by treatment (12.2% for andexanet alfa vs 25.0% for PCC; RR, 0.49; 95% CI, 0.21–1.16). Conclusions: In this propensity score–matched comparison across 2 independent datasets, adjusted 30‐day mortality rates were lower for patients treated with andexanet alfa than in matched patients receiving PCC. This indirect comparison was limited in that it could not account for several highly predictive variables including GCS score, hematoma volume, and expected survival. Further research is warranted to confirm the mortality differences between reversal/replacement agents for DOAC‐related bleeding.